In-field evaluation of the impact of ageing and fading effects on annual radon concentration measurements for two different techniques. (28th November 2016) - Venoso, G; Ampollini, M; Antignani, S; Carpentieri, C; Bochicchio, F
Abstract: Measurements covering a 1 year period are often used and required by legislation to assess the average radon concentration within a house or a workplace. This kind of long-term measurement—generally carried out with techniques based on nuclear track detectors—can be affected by a reduction in sensitivity due to ageing and fading of latent tracks during the exposure period, thus resulting in an underestimation of the actual average concentration. In order to evaluate in field conditions the ageing and fading effects on annual radon concentration measurements, two different studies in a large sample of rooms in dwellings (162) and in workplaces (432) were conducted using two different techniques (detector and track read-out system): (i) CR-39 plastics readout with a fully automated image analysis system, and (ii) LR 115 films with a spark-counter for track counting. Study design and data analysis aimed to evaluate both the average and the variability of ageing and fading effects in real conditions, and to reduce and separate the contribution of measurement uncertainty to the observed variability. For the CR-39 based technique, the results show that radon concentration measurements over a 12month period are on average about 16% lower than those evaluated with measurements of two consecutive 6 month periods, implying the need for a correction factor to avoid measurement bias (i.e. underestimation) due to ageing and fading effects. The observed variability of ageing and fading effects among the sampled rooms is not negligible (coefficient of variation about 18%), although a considerable fraction is attributable to measurement uncertainty, which is presumably not related to ageing and fading. For the technique based on LR 115 spark counting, ageing and fading do not significantly affect the results of radon concentration measurement.